Why read Abdelmalek Sayad? - Santos, Gislene; Paes, Rafaela (Geografares, 2026)
This text reflects on the thinking of sociologist Abdelmalek Sayad, highlighting the relationship between migration, state thinking, and work. We highlight the interdependence between these categories and also the stages of emigration, namely: temporariness and return. Throughout the text, we appreciate the importance of his work for the analysis of migration in the contemporary world, especially when we consider the political and methodological perspectives of this production.